Dissecting the biological heterogeneity of HER2-positive breast cancer. (October 2021) - Schettini, Francesco; Prat, Aleix
Abstract: HER2-positive (HER2+) breast cancer (BC) is a heterogenous and multifaceted disease, with interesting therapeutic implications. First, all intrinsic molecular subtypes can be identified in HER2+ tumors, with the HER2-enriched being the most frequent. Such subtypes do not differ much from their counterparts in HER2-negative disease, apart for the high expression of genes in/near the HER2 amplicon on chromosome 17. Intrinsic subtyping, along with the quantification of ERBB2 mRNA levels, is associated with higher rates of pathologic complete response across neoadjuvant trials of dual HER2 blockade and might help select patients for de-escalation and escalation treatment strategies. Secondly, HER2+ tumors have a broad range of DNA alterations. ERBB2 mutations and alterations in the PI3K/Akt/mTOR pathway are among the most frequent and might predict benefit from potent pan-HER, PI3K and mTOR inhibitors. Moreover, HER2+ tumors are usually infiltrated by lymphocytes. These tumor infiltrating-lymphocytes (TILs) predict response to neoadjuvant anti-HER2-based treatment and exert a prognostic role. PD-L1, detected in ∼42 % of HER2+ BC, might also be useful to define patients responding to novel anti-PD1/PD-L1 immunotherapies. New multiparametric clinicopathologic and genomic tools accounting for this complexity, such as HER2DX, are under development to define more tailored treatment approaches. Finally, HER2-targeted antibody-drug conjugates (ADC) such as trastuzumab deruxtecan might be active in tumors with low expression of HER2. Overall, there is a need to molecularly characterize and develop novel targeted therapies for HER2+ disease. Highlights: Almost 50 % of HER2+ breast cancer (BC) are molecularly HER2-Enriched (HER2-E). Most relevant mutations are found in ERBB2 (∼4 %) and PI3K/AKT/mTOR pathway (>30 %). Tumor infiltrating lymphocytes are frequent, predictive and prognostic in HER2+ BC. HER2 heterogeneity and HER2 low status are gaining therapeutic relevance. New treatments need to consider HER2+ molecular and microenvironmental complexity.